SMAK. Highlights for a Future : De Collectie. - Van Cauteren, Philippe; Verhoeven, Thibaut; Paschalidis, Iris; Armstrong, Richard (Gent : SMAK, 2019)
Alÿs, Francis ; Attia, Kader ; bacon, francis ; Baghramian, Nairy ; Barrio, Artur ; Beuys, Joseph ; Birnbaum, Dara ; Borremans, Michaël ; Broodthaers, Marcel ; Canell, Nina ; De Bruyckere, berlinde ; Dumas, Marlene ; Garabedian, Mekhitar ; Hammons, David ; Janssens, Ann veronica ; Leirner, Jac ; Sasnal, Wilhelm ; Tuymans, Luc ; Tayou, Pascale Marthine ; Panamarenko
Overzichtscatalogus SMAK collectie
boek